Failed Citizenship and Transformative Civic Education - Banks, James A. (Educational Researcher, 2017)
Global migration, the quest by diverse groups for equality, and the rise of populist nationalism have complicated the development of citizenship and citizenship education in nations around the world. Many racial, ethnic, cultural, linguistic, and religious groups are denied structural inclusion into their nation-state. Consequently, they do not fully internalize the values and symbols of the nation-state, develop a strong identity with it, or acquire political efficacy. They focus primarily on particularistic group needs and goals rather than the overarching goals of the nation-state. I conceptualize this process as failed citizenship and present a typology that details failed, recognized, participatory, and transformative citizenship. I describe the role of the schools in reducing failed citizenship and helping marginalized groups become efficacious and participatory citizens in multicultural nation-states.